Noise Mapping and Assessment of the Acoustic Environment in Coastal Puducherry, an Old French City: A Cross-Sectional Study - Venkatesan, Dr. Vijayabaskar; Gupta, Dr. Richa; Singh, Dr. Nikhilesh; ArunTipandjan, Dr.; SaravananAyyavoo, Dr.; S, Dr Krishnan (International Journal of Aquatic Research and Environmental Studies, 2026)
Introduction: According to the Central Pollution Control Board (CPCB) National Ambient Noise Monitoring Network data (2019), about 90 % of monitoring stations in major Indian cities recorded noise levels above the accepted limits, both during day and night. Urban environments like Puducherry exhibit complex spatial and temporal variations in noise pollution due to diverse land use patterns, dense traffic networks, and mixed residential-commercial zones.  Aim: This study aims to enhance ambient noise mapping across Puducherry’s through the geospatial analysis techniques to identify the hot spots in Urban area of Puducherry. Methods and Materials: Cross-sectional research was undertaken in October 2023 in Puducherry's urban areas. The grid size was established by the physics rule, which stipulates that increased vehicle traffic causes higher levels of noise. Spatial analysis was conducted at preliminary 2-hour static monitoring at three suspected noise sources, Coefficient of variation CV
Keywords: Noise pollution mapping, Geographic Information Systems, Geospatial, Spatial -temporal pattern, Puducherry